EXPERIMENTAL STUDY OF VARIABILITY OF THERMAL CONDUCTIVITY OF INSULATION MATERIALS (Academic journal Industrial Machine Building Civil Engineering, 2017)
Those buildings and thermal isolation materials like foam polystyrene and mineral wool, plasterboard sheets and OSB, and also polystyrene concrete are used for effective thermal isolation of building envelopes in light steel thin-walled structures building technology. Results of experimental studies of effective thermal these thermal insulation materials are shown. The results of previous research were confirmed, namely: thermal conductivity coefficient of thermal isolation materials can be shown in shape of normally distributed random variables. Results of experimental studies have been shown that standard value of thermal conductivity coefficient is located in limits from 0,0009 W/mK – for foam polystyrene with density ρ = 25 kg/m3 to 0,0351 W/mK – for polystyrene concrete B5 with density ρ = 1107 kg/m3. The coefficient of variation in the range from 1,79% – for polystyrene concrete B5 with density 1292 kg/m 3 to 10,57% – for polystyrene concrete B5 with density ρ = 1107 kg/m 3.